2010
DOI: 10.1261/rna.2185710
|View full text |Cite
|
Sign up to set email alerts
|

Mutations at the accommodation gate of the ribosome impair RF2-dependent translation termination

Abstract: During protein synthesis, aminoacyl-tRNA (aa-tRNA) and release factors 1 and 2 (RF1 and RF2) have to bind at the catalytic center of the ribosome on the 50S subunit where they take part in peptide bond formation or peptidyl-tRNA hydrolysis, respectively. Computer simulations of aa-tRNA movement into the catalytic site (accommodation) suggested that three nucleotides of 23S rRNA, U2492, C2556, and C2573, form a ''gate'' at which aa-tRNA movement into the A site is retarded. Here we examined the role of nucleoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 25 publications
5
22
0
Order By: Relevance
“…In addition, a recent study suggested that peptide bond formation and not accommodation may actually be the rate-limiting step in the translation elongation cycle (Johansson et al 2011). The observations that mutation of critical bases in the tRNA accommodation corridor did not affect accommodation rates (Burakovsky et al 2010), coupled with the observations in the present study, support this notion.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In addition, a recent study suggested that peptide bond formation and not accommodation may actually be the rate-limiting step in the translation elongation cycle (Johansson et al 2011). The observations that mutation of critical bases in the tRNA accommodation corridor did not affect accommodation rates (Burakovsky et al 2010), coupled with the observations in the present study, support this notion.…”
Section: Discussionsupporting
confidence: 88%
“…This suggests that rRNA in these functional regions of the ribosome formed compensatory rearrangements in response to single base substitutions at targeted positions. This further supports the idea that the ribosome is a robust machine (Burakovsky et al 2010) and can adjust its structure to preserve function.…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…Indeed, mutagenesis studies [61] indicated that substitutions of residues U2492 and U2555 at the accommodation gate decreased the fidelity of translation, supporting the view that the accommodation gate may attenuate aa-tRNA binding. However, mutations of C2573 and the neighbouring A2572 did not affect aa-tRNA accommodation, peptide bond formation or the fidelity of aa-tRNA selection, suggesting that the ribosome may allow rapid aa-tRNA accommodation in spite of defects at the accommodation gate, perhaps by using a different pathway [62]. Alternatively, misalignment of the near-cognate tRNA may disturb the network of interactions between tRNA and ribosome [56], thereby disfavouring accommodation and favouring rejection.…”
Section: The Crucial Forward Steps Of Decodingmentioning
confidence: 96%